1993
DOI: 10.1055/s-2007-1002179
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine-Supported Oxidation in the Myeloperoxidase System

Abstract: Thyroxine and other iodothyronines (concentrations in the nanomolar range) stimulated the oxidation of NADH in the myeloperoxidase-H2O2-Cl- system. In the absence of chloride, thyroxine had only a marginal effect. This suggests that thyroxine increased the generation of chlorinating oxidants. A peroxidase-catalysed oxidation product of thyroxine, 3,5-diiodotyrosine, was inactive. Pre-incubation of thyroxine in the myeloperoxidase system showed that thyroxine was oxidized to a product capable of stimulating NAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Although thyroxine can substitute for the halide in the MPO-H 2 O 2 -halide antimicrobial system [69], throxine is deiodinated under these conditions [204,205], raising the possibility that the released iodide may be the required microbicidal component. The thyroid hormones have, however, been reported to stimulate the generation of chlorinating oxidants by the MPO-H 2 O 2 -chloride system [383,384]. Impaired thyroid hormone or estrogen response has not been noted in patients with MPO deficiency, suggesting that the phenolic hormones do not require MPO for their action.…”
Section: Other Beneficial Functions Of Mpomentioning
confidence: 99%
“…Although thyroxine can substitute for the halide in the MPO-H 2 O 2 -halide antimicrobial system [69], throxine is deiodinated under these conditions [204,205], raising the possibility that the released iodide may be the required microbicidal component. The thyroid hormones have, however, been reported to stimulate the generation of chlorinating oxidants by the MPO-H 2 O 2 -chloride system [383,384]. Impaired thyroid hormone or estrogen response has not been noted in patients with MPO deficiency, suggesting that the phenolic hormones do not require MPO for their action.…”
Section: Other Beneficial Functions Of Mpomentioning
confidence: 99%
“…39 However, T4 was found to be ineffective in the absence of Cl Ϫ , thus suggesting that the hormone stimulated HOCl generation. 41,42 It has been reported by Durmuş et al 43 that the elevation in the intraperitoneal concentration of the bacteria caused thyroid hormones to decline in experimentally developed sepsis.…”
Section: Discussionmentioning
confidence: 98%
“…3 Van Zyl et al 41,42 showed that leukocytes concentrated iodine. The preincubation of thyroxine in the myeloperoxidase system showed thyroxine to be oxidized to a product capable of stimulating NADH oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation